The impact of the idea gardens strategy on the achievement of fifth- grade literary student in the subject of psychology and the development of their logical thinking - AL-Haddad, Bakr Farooq Sulaiman; Al-Samurai, Qusay Mohammad Latif (Al-Adab Journal, 2021)
This research aims to identify (the impact of the idea gardens strategy on the achievement of fifth-grade literary students in the subject of psychology and the development of their logical thinking) To achieve the goal of the research, the researcher developed the zero hypotheses. The researcher adopted the experimental approach with the two experimental and controlling equal groups and selected a sample of literary fifth graders in Samarra intentionally and chose a school Dubi and Al-Zahrawie in a simple random way. The experimental group and the number of its students is (30) students studying the subject of principles of philosophy and psychology with the idea gardens strategy. The control group and its number of students is (30) students studying the subject of principles of philosophy and psychology in the traditional way. The researcher rewarded between the two research groups in the variables (intelligence, temporal age, grade point average for the previous year for the fourth literary grade, father’s academic achievement, mother’s academic achievement, logical thinking), and after the researcher identified the scientific subject to be taught that included the subject of principles of philosophy and psychology for the class The literary fifth, to be taught for the academic year (2020-2021). In light of this, the researcher prepared behavioral goals of (79) goals according to Bloom levels (remember, understand, apply, analyze) and prepared educational plans with (16) daily plans for each of the two research groups. The researcher prepared a test for acquiring concepts of the type (multiple choice) consisting of (30) paragraphs after specifying (10) concepts for the subject matter and a test of logical thinking skills, amounting to (28) paragraphs within four skills or areas which are (logic of cases, logical mental trial, Deductive groups. thinking, the relationship between probability and realism) has been verified for its honesty (apparent and content), its discriminatory strength, its difficulty factor, and the effectiveness of wrong alternatives, while persistence has been extracted in the two methods of the Koder-Reedhardson-20 equation and the (Alpha-Kronbach),. The procedures of the experiment continued (10) weeks, at the end of which a test for acquiring post-concepts was applied. After two days, the test was applied to measure logical thinking skills. The researcher used the appropriate statistical means and the study yielded the following results: The experimental group that studied the strategy of gardens of ideas gained superiority over the acquisition of concepts over the control group that was studied in the traditional way. The experimental group that studied the "Gardens of Ideas" strategy by logical thinking is superior to the control group that was studied in the traditional way.